Historical fates of the libraries of the Roman-Catholic friaries of the Volyn province in the light of the cassations in 1832 by the Russian state authorities - Tsiborovska-Rymarovych Iryna Olehivna (Рукописна та книжкова спадщина України, 2018)

(untitled)
The publication is devoted to the historical destinies of the libraries of the Roman Catholic friaries of Volyn province, which were abolished after the suppression of the Polish uprising of 1830-1831 under a tzar’s ukase “About the dissolution of some Catholic friaries” dated the 19th of July of 1832. By the end of 1832 according the tzar’s ukase 35 Catholic friaries in the Volyn province were closed. They belonged to the nine monastic orders, namely: Bernardines, Franciscans, Barefooted Carmelites, Shoed Carmelites, Augustinians, Capuchins, Dominicans, Trinitarians and Marians. On the basis of archival documents stored in the f. 442, the Office of the Kyiv, Podillia and Volyn Governor-General in the Central State Historical Archives of Ukraine in Kyiv, the organization and mechanism of the transfer of the libraries’ stocks to various secular and clerical institutions and organizations were highlighted. Requirements for the compilation of the lists of books from the libraries of the dissolved friaries are stated. The role of professors of the University of St. Volodymyr and the librarian of the university’s library in the solving the question of the fate of the books from the dissolved friaries in the Volyn, Podillia and Kiyv provinces are elucidated. On the basis of heuristic work with the fund of Vernadsky National Library of Ukraine and a source-analysis of the old-printed books from the book collections of Roman Catholic monasteries, the books from the libraries of the abandoned Roman Catholic friaries of Volyn province in different amounts were erected. Those are from the Berestechko and the Teofipol monasteries of the Trinitarian Order, the Augustine monastery in Codnia, the Mezhyrych monastery of Scholarum Piarum, the Ostrog Capuchin monastery, the Vishnevetsky monastery of the Order of the Barefooted Carmelites, the Chudniv and the Ianiv Bernardine monasteries.